Figurative Language in The Broken WingsBy Kahlil Gibran a PragmaticPerspective - Ardy Waskitha, Ginanjar, Dr. Maryadi, M.A, Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
This study is about figurative language. This research is a descriptive qualitative research in which the objective is to describe the actual user of language for communication. The objectives of this research are: To identify the types of figurative language used in The Broken Wings by Kahlil Gibran; and to examine the intention of figurative language used in The Broken Wings by Kahlil Gibran. The data of the research is the sentence that contains a figurative language in Kahlil Gibran's novel. The data taken from The Broken Wings by Kahlil Gibran. There were 70 sentences of figurative language. It shows Simile 40 sentences (57%), Personification 15 sentences (22%), Metaphor 2 sentences (3%), Metonymy 10 sentences (14%), and Synecdoche 3 sentences (4%). There are 51 sentences are Assertive (73%); 4 sentences are Directive (6%), content of advice; 3 sentences are Commisive (4%); 11 sentence are expressive (16%); and 1 sentence is Declaration (1%).